The Impact of Self-Care Management on Systolic Blood Pressure Control in Hypertensive Patients - Faqih, Moh. Ubaidillah; Munir, Miftahul; Hakim, Lukman; Putri, Berlian Maharani Febrina (PT. Pubsains Nur Cendekia, 2025)
Background: Systolic blood pressure is an important indicator in the diagnosis of hypertension and plays a significant role in heart disease, stroke, and kidney failure. Hypertension can be managed through a healthy lifestyle and medication; however, consistency in applying self-care is a major challenge. Aims: To determine the relationship between self-care management and systolic blood pressure in hypertensive patients. Methods: A descriptive correlational study design with a cross-sectional approach was conducted with 112 hypertensive respondents. Self-care management data were collected using the Hypertension Self Management Behavior Questionnaire, and systolic blood pressure was measured with a digital sphygmomanometer. The data were analyzed using the Spearman test. Results: The majority of hypertensive patient had self-care management in the